2002
DOI: 10.1111/j.1749-6632.2002.tb04696.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Signaling by Glutathione and Its Novel Analogue through Potent Stimulation of Frontocortical G Proteins in Normal Aging and in Alzheimer's Disease

Abstract: In the frontal cortex (FC) of the normally aging human brain, glutathione (GSH) and its novel analogue, UPF1, stimulate G proteins more than in Alzheimer's disease (AD) FC. In normal aging and in AD, UPF1 is a more efficient stimulator of G proteins than GSH. In normal FC, both GSH and UPF1 stimulate G proteins, which mediate inhibitory signals to the cAMP system; while in AD, only UPF1 exhibits the same action. Stimulation of G proteins and coupled signaling by GSH antioxidant analogues, as potential signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 5 publications
(6 reference statements)
2
23
0
Order By: Relevance
“…In our previous studies we have shown that UPF1 modulates the activity of the G-proteins in the brain tissue [12] and can act as a scavenger [6] or a signal molecule increasing the level of glutathione itself or the glutathione redox ratio (our unpublished data).…”
mentioning
confidence: 76%
“…In our previous studies we have shown that UPF1 modulates the activity of the G-proteins in the brain tissue [12] and can act as a scavenger [6] or a signal molecule increasing the level of glutathione itself or the glutathione redox ratio (our unpublished data).…”
mentioning
confidence: 76%
“…Oxidative stress causes profound alterations of various biological structures including cellular membranes, lipids, proteins and nucleic acids. Oxidative stress is considered to be involved in aging [44][45][46][47][48][49][50][51] and in various diseases such as diabetes mellitus [52][53][54], atherosclerosis [55,56], rheumatoid arthritis [57][58][59][60], Alzheimer's disease [61][62][63], Parkinson's disease [64][65][66] and cancer [67][68][69][70][71]. There is an increasingly growing interest in identifying biomarkers for diseases in which oxidative stress is involved [72].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Nevertheless, the effects of GSH to motor neuron degeneration in ALS remains largely unknown, even though abnormalities in GSH are associated with pathophysiological mechanisms underlying neuronal loses in both Parkinson's disease and Alzheimer's disease (Paik et al, 2003;Jha et al, 2000;Karelson et al, 2002;Cecchi et al, 1999). To this end, we measured the GSH and GSSG levels in the spinal cord lumbar region of G93A-SOD1 transgenic mice at three defined stages, namely, disease free, disease onset and disease progression.…”
Section: Decreased Gsh Is Associated With Motor Neuron Degeneration Amentioning
confidence: 99%
“…On the other hand, because BSO does not completely deplete mitochondrial and nuclear GSH, other agents, including ethacrynic acid (EA) have been used to effectively deplete cellular, mitochondrial and nuclear GSH (Keelan et al, 2001;Rizzardini et al, 2003). Alterations in GSH synthesis, or in GSH pools, have been associated with neuronal cell death and mimic a variety of human neurodegenerative diseases, such as Parkinson's disease (Bharath et al, 2002;Jha et al, 2000;Mytilineou et al, 2002;Paik et al, 2003), Alzheimer's disease (Adams, Jr. et al, 1991;Cecchi et al, 1999;Janaky et al, 1999;Karelson et al, 2002) and Schizophrenia (Do et al, 2000). Nevertheless, the role of GSH in the pathogenesis of motor neuron degeneration in ALS remained largely undefined.…”
Section: Introductionmentioning
confidence: 99%